Thermal niche diversity and trophic redundancy drive neutral effects of warming on energy flux through a stream food web. Issue 4 (11th March 2020) - Nelson, Daniel; Benstead, Jonathan P.; Huryn, Alexander D.; Cross, Wyatt F.; Hood, James M.; Johnson, Philip W.; Junker, James R.; Gíslason, Gísli M.; Ólafsson, Jón S.
Abstract: Climate warming is predicted to alter routing and flows of energy through food webs because of the critical and varied effects of temperature on physiological rates, community structure, and trophic dynamics. Few studies, however, have experimentally assessed the net effect of warming on energy flux and food web dynamics in natural intact communities. Here, we test how warming affects energy flux and the trophic basis of production in a natural invertebrate food web by experimentally heating a stream reach in southwest Iceland by 4°C for 2 yr and comparing its response to an unheated reference stream. Previous results from this experiment showed that warming led to shifts in the structure of the invertebrate assemblage, with estimated increases in total metabolic demand but no change in annual secondary production. We hypothesized that elevated metabolic demand and invariant secondary production would combine to increase total consumption of organic matter in the food web, if diet composition did not change appreciably with warming. Dietary composition of primary consumers indeed varied little between streams and among years, with gut contents primarily consisting of diatoms (72.9%) and amorphous detritus (19.5%). Diatoms dominated the trophic basis of production of primary consumers in both study streams, contributing 79–86% to secondary production. Although warming increased the flux of filamentous algae within the food web, total resource consumption did not increase as predicted. The neutral net effect of warming on total energy flow through the food web was a result of taxon‐level variation in responses to warming, a neutral effect on total invertebrate production, and strong trophic redundancy within the invertebrate assemblage. Thus, food webs characterized by a high degree of trophic redundancy may be more resistant to the effects of climate warming than those with more diverse and specialized consumers.